Risk of congenital malformations among children of construction painters in Denmark: a nationwide cohort study - Ninna Hahn Tougaard; Jens Peter Bonde; Karin Sørig Hougaard; Kristian Tore Jørgensen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: Painters' occupational exposure is classified as a group 1 carcinogen by the International Agency for Research on Cancer (IARC). Previous studies have shown increased risk of congenital malformations among children of women exposed to organic solvents and paint emissions during pregnancy. In Denmark, women comprise half of those enrolled in vocational paint training. We investigated the association between maternal and paternal occupational painting, respectively, and the risk of congenital malformations among children. METHODS: National register data were used to link childbirths, malformations, and parental occupation. The cohort included >1 300 000 children born to occupationally active women in Denmark 1980-2010. Cases were hospital-diagnosed with malformations within the first year of life. Odds ratios (OR) with 95% confidence intervals (95% CI) were estimated using multiple logistic regression with adjustment for potential confounders. RESULTS: Among 3444 children of female construction painters, we found no increased risk of malformations overall (126 cases, OR 0.88, 95% CI 0.74-1.05) or in organ-specific subgroups compared to children of women in all other occupations (55 045 cases). Sensitivity analyses restricted to severe malformations, children of maternal painters with ≥2 years of pre-pregnancy exposure, and firstborn children, and analyses with maternal healthcare assistants and kitchen workers as reference supported the main results. Also, no associations were found when including diagnoses within the first 10 years of life, when stratifying by maternal age, birth year, and sex, or for paternal construction painters. CONCLUSIONS: This nationwide cohort study is reassuring with no indications of increased risk of congenital malformations among children of male or of female construction painters.